Designing Video-Based Speaking Materials to Promote Flipped Classroom Practices in EFL Teaching - Asrilawaly, Syabitha; Ciptaningrum, Dyah Setyowati; Niah, Siti (JOLLT Journal of Languages and Language Teaching, 2025)
The flipped classroom model redefines traditional teaching by enabling students to engage with course material before class, therefore optimizing in-class time for interactive learning activities. This paradigm utilizes digital technology to provide personalized immersive experiences that align with studentsâ€™ digital behaviors and varied learning preferences, making it particularly relevant in EFL contexts where communicative practice is crucial. Â This study sought to provide video-based supplemental speaking resources to facilitate the implementation of a flipped classroom model for eleventh-grade students. The study used a Research and Development (R&D) approach based on the Jolly and Bolitho (1998) framework, including several stages: need analysis, contextual and pedagogical realization, material production, implementation in the classroom, and evaluation. The data gathering included qualitative techniques, including interviews and document analysis, alongside quantitative approaches, such as student and expert questionnaires. The outcome materials tackled essential speaking challengesâ€”fluency and intonationâ€”utilizing authentic audio resources and pronunciation exercises, with topics customized to student interests to augment motivation and participation. The flipped model integrated online pre-class and in-class activities, facilitating systematic practice, immediate feedback, and active participation. The findings indicated that the materials fostered an inclusive learning environment, reinforced student confidence, and improved vocabulary and speaking skills, particularly among beginners. Expert evaluations classified the materials as â€œvery appropriateâ€ with a mean score of 3.4, within the 3.26 < x â‰¤ 4.00 rangee. These results indicate that meticulously designed video-based materials may effectively enhance flipped EFL classes and promote substantial language acquisition.Â 